2018
DOI: 10.3390/ijms19020357
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping by Sequencing Highlights a Polygenic Resistance to Ralstonia pseudosolanacearum in Eggplant (Solanum melongena L.)

Abstract: Eggplant cultivation is limited by numerous diseases, including the devastating bacterial wilt (BW) caused by the Ralstonia solanacearum species complex (RSSC). Within the RSSC, Ralstonia pseudosolanacearum (including phylotypes I and III) causes severe damage to all solanaceous crops, including eggplant. Therefore, the creation of cultivars resistant to R. pseudosolanacearum strains is a major goal for breeders. An intraspecific eggplant population, segregating for resistance, was created from the cross betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…is an important economic crop worldwide, and VW caused by V. dahliae , results in significant annual economic losses through reduced boll quality and quantity. Improving genetic resistance is the preferred method of managing VW in most crops ( Schaible et al, 1951 ; Putt, 1964 ; Simko et al, 2004 ; Bolek et al, 2005 ; Zebrowska et al, 2006 ; Li et al, 2017 ), but identifying this resistance is difficult because of the unavailability of resistance genes against this pathogen. However, several genes that contribute to the defense response against VW have been reported in cotton, including GbCAD1 and GbSSI2 ( Gao et al, 2013 ), GbaNA1 ( Li et al, 2018 ), GbSTK ( Zhang Y. et al, 2013 ), GbTLP1 ( Munis et al, 2010 ), and GbNRX1 ( Li et al, 2016 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…is an important economic crop worldwide, and VW caused by V. dahliae , results in significant annual economic losses through reduced boll quality and quantity. Improving genetic resistance is the preferred method of managing VW in most crops ( Schaible et al, 1951 ; Putt, 1964 ; Simko et al, 2004 ; Bolek et al, 2005 ; Zebrowska et al, 2006 ; Li et al, 2017 ), but identifying this resistance is difficult because of the unavailability of resistance genes against this pathogen. However, several genes that contribute to the defense response against VW have been reported in cotton, including GbCAD1 and GbSSI2 ( Gao et al, 2013 ), GbaNA1 ( Li et al, 2018 ), GbSTK ( Zhang Y. et al, 2013 ), GbTLP1 ( Munis et al, 2010 ), and GbNRX1 ( Li et al, 2016 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the resistances in S. melongena EG203 and S. incanum UPV1 and the moderate resistance of S. anguivi UPV3 against strain Pss2016 must be controlled by a recessive gene(s). However, Salgon et al [ 22 ] found that in an intraspecific cross, the resistance of EG203 was dominant, although strains of R. solanacearum different to ours were used. This suggests that the mode of inheritance of the resistance of EG203 to bacterial wilt depends, either on the strain, the genetic background, or both.…”
Section: Resultsmentioning
confidence: 81%
“…Host resistance to R. solanacearum has been studied in eggplant since the 1960s in eggplant [ 17 , 18 , 19 ], and molecular markers linked to the resistance of several sources have been developed [ 20 , 21 ]. A recent study [ 22 ] detected several QTLs associated with resistance to phylotypes I and III in the cross between the resistant EG203 accessions and a susceptible eggplant, although QTLs expression was highly influenced by environmental conditions. Wild relatives have been frequently used in the genetic improvement of many crops, as sources for resistance to biotic and abiotic stresses and also for quality traits [ 23 , 24 ], as well as for the development of rootstocks.…”
Section: Introductionmentioning
confidence: 99%
“…The genomic regions associated with bacterial wilt resistance on chromosome 6 in both Hawaii 7996 and L285 were co-localized. Furthermore, the most stable QTL for bacterial wilt resistance in eggplant was also identified in chromosome 6 and syntenic with Bwr-6 of tomato ( Salgon et al 2018 ). All these suggest the significance of Bwr-6 in bacterial wilt resistance in tomato and likely in other Solanaceae crops.…”
Section: Discussionmentioning
confidence: 98%